1985
DOI: 10.1530/jrf.0.0740023
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of sperm motility and its maintenance during storage in the lizard, Lacerta vivipara

Abstract: Summary. Lizard spermatozoa, which are non-motile in the testis, develop the ability to swim as they pass along the excurrent duct. The addition of caffeine, a phosphodiesterase inhibitor, induced forward motility in spermatozoa from the caput epididymidis and increased the velocity of spermatozoa from the distal part of the epididymis. Caffeine had no effect on the motility of testicular spermatozoa. This suggests that sperm motility in this species is cyclic AMP-dependent but this factor alone is not suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 7 publications
3
29
0
1
Order By: Relevance
“…Besides maturation, the posterior segment also acts as site for accumulation, as evident from the considerably high sperm index in this region. On the basis of the present findings and other investigations in H. jluviviridis [4] and L. vivipuru [3] in which tubule and luminal diameters and sperm density have been the greatest, and epithelial height considerably lowest in the posterior region, the posterior region of wall lizard epididymis may be considered histologically as well as functionally a counterpart of cauda epididymis in mammals.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Besides maturation, the posterior segment also acts as site for accumulation, as evident from the considerably high sperm index in this region. On the basis of the present findings and other investigations in H. jluviviridis [4] and L. vivipuru [3] in which tubule and luminal diameters and sperm density have been the greatest, and epithelial height considerably lowest in the posterior region, the posterior region of wall lizard epididymis may be considered histologically as well as functionally a counterpart of cauda epididymis in mammals.…”
Section: Discussionsupporting
confidence: 69%
“…In reptiles, though the epididymis is not morphologically differentiated as in mammals, remarkable histological changes are reported among anterior, middle, and posterior regions of the lizard species Lacerta vivipara [3] and Hemidactylus jlaviviridis [4]. Histologically, anterior, middle, and posterior segments of epididymis are comparable to caput, corpus, and cauda of mammalian epididymis.…”
mentioning
confidence: 99%
“…Since, the earlier studies (L. vivipara, Depeiges and Dacheux, 1985;H. flaviviridis, Nirmal and Rai, 1997) and M. carinata (Aranha et al, 2008) have shown an increase in the percent forward progressive motility of the spermatozoa occurs during their transit from anterior to posterior end of the epididymis, it appears that the epididymal luminal fluid influences the progressive motility on passage through the epididymis.…”
Section: Discussionmentioning
confidence: 94%
“…There is no regional difference in secretory proteins of epididymal luminal fluid in Hemiductylus flaviviridis (Nirmal and Rai, 2000) whereas, it exists in Lacerta vivipara (Depeiges and Dacheux, 1985) and Mabuya carinata (Aranha et al, 2006). In M. carinata, the whole epididymal and the vas deferens Int.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional electrophoresis has made it possible to characterize a major band of Mr 19 000, called the L protein (Depeiges & Dufaure, 1981); its synthesis is androgen-dependent (Depeiges et al, 1981a). With an anti-L protein immunoserum, the presence of this protein was detected on the spermatozoa (Depeiges & Dufaure, 1983), which undergo epididymal maturation in this species (Depeiges & Dacheux, 1985) as in mammals.…”
Section: Introductionmentioning
confidence: 88%